2013
DOI: 10.3389/fmicb.2013.00140
|View full text |Cite
|
Sign up to set email alerts
|

In situ detection of anaerobic alkane metabolites in subsurface environments

Abstract: Alkanes comprise a substantial fraction of crude oil and refined fuels. As such, they are prevalent within deep subsurface fossil fuel deposits and in shallow subsurface environments such as aquifers that are contaminated with hydrocarbons. These environments are typically anaerobic, and host diverse microbial communities that can potentially use alkanes as substrates. Anaerobic alkane biodegradation has been reported to occur under nitrate-reducing, sulfate-reducing, and methanogenic conditions. Elucidating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 88 publications
1
50
0
Order By: Relevance
“…In contrast, members of the Deltaproteobacteria, particularly Syntrophus/Smithella sp., have been implicated in methanogenic alkane degradation, particularly of longer-chain alkanes (Zengler et al, 1999;Gray et al, 2011;Cheng et al, 2013). Indeed, all of the known strictly anaerobic (for example, sulfate-reducing/syntrophic) alkane degraders are Deltaproteobacteria (Mbadinga et al, 2011;Agrawal and Gieg, 2013;Callaghan, 2013). However, the implication of a Peptococcaceae in degradation of low molecular weight n-alkanes (for example, propane) under sulfate-reducing conditions (Kniemeyer et al, 2007) and iso-alkanes under methanogenic conditions (Abu Laban et al, in press; Tan et al, 2014B) supports a role for Firmicutes in anaerobic alkane degradation.…”
Section: Community Compositions Of Methanogenic Hydrocarbon-degradingmentioning
confidence: 99%
“…In contrast, members of the Deltaproteobacteria, particularly Syntrophus/Smithella sp., have been implicated in methanogenic alkane degradation, particularly of longer-chain alkanes (Zengler et al, 1999;Gray et al, 2011;Cheng et al, 2013). Indeed, all of the known strictly anaerobic (for example, sulfate-reducing/syntrophic) alkane degraders are Deltaproteobacteria (Mbadinga et al, 2011;Agrawal and Gieg, 2013;Callaghan, 2013). However, the implication of a Peptococcaceae in degradation of low molecular weight n-alkanes (for example, propane) under sulfate-reducing conditions (Kniemeyer et al, 2007) and iso-alkanes under methanogenic conditions (Abu Laban et al, in press; Tan et al, 2014B) supports a role for Firmicutes in anaerobic alkane degradation.…”
Section: Community Compositions Of Methanogenic Hydrocarbon-degradingmentioning
confidence: 99%
“…Using quantum chemical calculations, it has been shown that this reaction is exothermic and has an overall energy change around -40 kJ/mol [Beasley and Nanny, 2012]. Accordingly, n -alkylsuccinates (including methylsuccinate) occasionally detected in hydrocarboncontaining natural environments have been attributed to the terminal activation of n -alkanes [Agrawal and Gieg, 2013;Gieg et al, 2010].…”
Section: N-alkylsuccinates Are Not (Necessarily) Formed By Terminal Amentioning
confidence: 99%
“…Among recent discoveries are new mechanisms and enzymes involved in anaerobic alkane oxidation. In this issue, we have included review articles by Callaghan (2013) and Agrawal and Gieg (2013) outlining the current state of knowledge regarding anaerobic methane and non-methane alkane oxidation and methods for the in situ detection of anaerobic alkane biodegradation.…”
mentioning
confidence: 99%